2004
DOI: 10.1128/cdli.11.5.856-861.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photopheresis on Lymphocyte Population in Children with Newly Diagnosed Type 1 Diabetes

Abstract: In recent years photopheresis has been claimed to be an effective form of immunomodulation. It has also been shown to have an effect on the disease process at the onset of type 1 diabetes. In a double-blind, placebo-controlled randomized study, we analyzed if the effect of photopheresis in children with newly diagnosed diabetes is related to changes in the balance of lymhocyte populations. We also analyzed if lymphocyte subsets were related to recent infection, mild or aggressive disease manifestations, heredi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…The collected results are consistent with the earlier finding regarding lymphocyte activation [34]. Maintained levels of TGF-b mRNA expression taken together with increased IL-4 and IL-10 expression makes it possible to assume that it could be Tr1 cells that are active in this tolerance maintenance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The collected results are consistent with the earlier finding regarding lymphocyte activation [34]. Maintained levels of TGF-b mRNA expression taken together with increased IL-4 and IL-10 expression makes it possible to assume that it could be Tr1 cells that are active in this tolerance maintenance.…”
Section: Discussionsupporting
confidence: 91%
“…Previous results from our ECP trial also showed that treated individuals had increased levels of IL‐10 compared with placebo controls [27]. Additionally, there was an indication that activated CD4 + and CD8 + cells increased in the placebo controls during the course of the study, an increase that was not observed in the actively treated group [34].…”
Section: Discussionmentioning
confidence: 62%
“…In the present study, the size of T γδ populations in T1DM group ranged between 0.45% and 23.13%, was significantly (p = 0.042) lower than in healthy controls (4.1%-27.34%) and comparable to the level reported by Ernerudh [18]. Our observa- Control group tion could be explained by studies showing in NOD mice that a decreased level of T γδ cells caused diabetes development and the expansion of T γδ CD4 -CD8 + cells after aerosol insulin treatment was highly protective against auto aggression [6,19,20].…”
Section: Discussionsupporting
confidence: 74%
“…However, in the placebo group, the proportions of activated CD4 + and CD8 + cells increased over time, whereas such changes were not seen in the ECP‐treated group. These findings probably reflect an activation of lymphocytes as part of the natural course of T1D and that ECP may have some suppressant effects, preventing lymphocyte activation . ECP produced cytokine changes reflecting a Th2‐like response .…”
Section: Mode Of Actionmentioning
confidence: 91%